Aerosolized recombinant human butyrylcholinesterase delivered by a nebulizer provides long term protection against inhaled paraoxon in macaques. (25th August 2019) - Rosenberg, Yvonne; Fink, James; MacLoughlin, Ronan; Ooms-Konecny, Tara; Sullivan, Dennis; Gerk, William; Mao, Lingjun; Jiang, Xiaoming; Lees, Jonathan; Urban, Lori; Rajendran, Narayanan
Abstract: The recent intentional use of nerve agents and pesticides in Europe and Afghanistan highlights the need for an effective countermeasure against organophosphates (OP) toxins. The most developed pretreatment candidate to date is plasma (native) human butyrylcholinesterase (HuBChE), which is limited in availability and because of its 1:1 stoichiometry with OPs, a large dose will present challenges when delivered parenterally both in terms of pharmacokinetics and manageability in the field. A tetrameric recombinant (r) form of human BChE produced in CHO–K1 cells with similar structure, in vivo stability and antidotal efficacy as the native form, has been developed to deliver rHuBChE as an aerosol (aer) to form a pulmonary bioshield capable of neutralizing inhaled OPs in situ and prevent AChE inhibition in the blood and in the brain; the latter associated with the symptoms of OP toxicity. Previous proof-of-concept macaque studies demonstrated that delivery of 9 mg/kg using a microsprayer inserted down the trachea, resulted in protection against an inhaled dose of 15ug/kg of aer-paraoxon (aer-Px) given 72 h later. In the present studies, pulmonary delivery of rHuBChE in macaques was achieved using Aerogen vibrating mesh nebulizers, similar to that used for human self-administration. The promising findings indicate that despite the poor lung deposition observed in macaques using nebulizers (13–20%), protective levels of RBC-AChE were still present in the blood even when exposure aer-Px (55 μg/kg) was delayed for five days. This long term retention of 5 mg/kg rHuBChE deposited in the lung bodes well for the use of an aer-rHuBChE pretreatment in humans where a user-friendly customized nebulizer with increased lung deposition up to 50% will provide even longer protection at a lower dose. Highlights: Generation of protective "pulmonary bioshield" using aerosolized rHuBChE against inhaled paraoxon in macaques. Pulmonary delivery using Aerogen Solo vibrating mesh nebulizer (VMN). Deposited rHuBChE persists in the lungs for 5 days. Lung deposition and duration of protection increased using modified Solo VMN.